Thermal Buckling and Thermal Induced free Vibration Analysis of Perforated Composite Plates: a Mathematical Model - Sina Soleimanian; Ali Davar; Jafar Eskandari Jam; Mohammad Reza Zamani; Mohsen Heydari Beni (Mechanics of Advanced Composite Structures)
This artcile is concerned with thermal buckling and thermal induced free vibration analyses of PCPs (perforated composite plates) with simply supported edges applying a mathematical model. The stiffness and density of PCP are defined locally using Heaviside distribution functions. The governing equations are derived based on CLPT. The present solution gives reasonable results in comparison with the few literatures. In order to inspect the structural behaviour of PCPs subjected to initial thermal loads, many parametric studies have been carried out. Results indicated that the presence of perforations has a significant effect on thermal buckling and thermal induced fundamental frequency.